2021
DOI: 10.3390/polym13213719
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Chemical and Physical Characteristics of an Edible Film Based on Native Potato Starch and Nopal Mucilage

Abstract: Edible films prepared from biological materials are being massively used. This study aimed to prepare edible films from native potato starch of the Allcca sipas variety (Solanum tuberosum subsp. Andigena), nopal mucilage (Opuntia ficus indica), and glycerol. Twelve edible films were prepared with starch, mucilage, and glycerin in different proportions by thermosynthesis. It was observed that mucilage and glycerol have a significant direct effect on film solubility and an inverse effect on aw, while the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…The thermal behavior of nostoc, shown in Figure 4 , shows three stages of decomposition. The first one is related to the loss of free and bound water [ 41 , 57 , 58 ], linked to the carbohydrates of the hydrocolloids in the dehydrated and spray-dried nostoc; this stage happens up to around 100 °C, although the spray-dried CE and CH report 85.31 and 78.67 °C, respectively ( Table 7 ). It was observed that the spray-dried CR sample lost less amount of water (7.44%), while the CE, CH, and CQ samples reported water losses of 12.56, 12.19, and 13.02%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal behavior of nostoc, shown in Figure 4 , shows three stages of decomposition. The first one is related to the loss of free and bound water [ 41 , 57 , 58 ], linked to the carbohydrates of the hydrocolloids in the dehydrated and spray-dried nostoc; this stage happens up to around 100 °C, although the spray-dried CE and CH report 85.31 and 78.67 °C, respectively ( Table 7 ). It was observed that the spray-dried CR sample lost less amount of water (7.44%), while the CE, CH, and CQ samples reported water losses of 12.56, 12.19, and 13.02%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The second stage is related to the decomposition of low molecular weight carbohydrates and peptides due to the depolymerization of their unit molecules; these happen at around 300 °C [ 57 , 58 , 59 ]. In this same stage, the decomposition of hydrocolloids (series of mono and disaccharide sugars) occurs, due to the breaking of glycosidic bonds, mainly mannose and galactose, of the -C-C, -CO type [ 41 , 42 ], which happens around 200 °C [ 43 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the band 1610 cm -1 is assigned to COO -(carboxylate ion) (Rodríguez-González et al, 2014). A set of bands with absorbances between 1408 and 1247 cm -1 can be assigned to the C-H or -OH bonds of alcohol groups (Choque-Quispe et al, 2021). Furthermore, a higher intensity was observed in the band around 1047 cm -1 , observed as C-O stretching corresponding to alcohols, carboxylic acids, esters, and ethers (Pavia et al, 2008;Silverstein et al, 2014).…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Potato ( Solanum tuberosum ) and sweet potato ( Ipomoea batatas ) are tubers belonging to the Solanaceae and Convolvulaceae families, respectively. Both potato and sweet potato are good sources of starch, an adequate alternative for developing edible films presenting numerous advantages, including low cost, renewability, availability, edibility, good film‐forming and degradability (Choque‐Quispe et al ., 2021; Charles et al ., 2022). Moreover, depending on the variety, potato and sweet potato contain different bioactive compounds such as pigments, dietary fibre, vitamins and minerals demanded by consumers (Martínez‐Prigadá et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%